Coking-Resistant Iron Catalyst in Ethane Dehydrogenation Achieved through Siliceous Zeolite Modulation - Yang, Zhiyuan; Li, Huan; Zhou, Hang; Wang, Liang; Wang, Lingxiang; Zhu, Qiuyan; Xiao, Jianping; Meng, Xiangju; Chen, Junxiang; Xiao, Feng-Shou (Journal of the American Chemical Society, 2020)
Nonoxidative dehydrogenation is promising for production of light olefins from shale gas, but current technology relies on precious Pt or toxic Cr catalysts and suffers from thermodynamically oriented coke formation. To solve these issues, the earth-abundant iron catalyst is employed, where Fe species are effectively modulated by siliceous zeolite, which is realized by the synthesis of Fe-containing MFI siliceous zeolite in the presence of ethylenediaminetetraacetic sodium (FeS-1-EDTA). Catalytic tests in ethane dehydrogenation show that this catalyst has a superior coke resistance in a 200 h run without any deactivation with extremely high activity and selectivity (e.g., 26.3% conversion and over 97.5% selectivity to ethene in at 873 K, close to the thermodynamic equilibrium limitation). Multiple characterizations demonstrate that the catalyst has uniformly and stably isolated Fe sites, which improves ethane dehydrogenation to facilitate the fast desorption of hydrogen and olefin products in the zeolite micropores and hinders the coke formation, as also identified by density functional calculations.